Effects of urea topdressing time on yield, nitrogen utilization, and quality of mechanical direct-seeding hybrid indica rice under slow-mixed fertilizer base application - Sun, Yongjian; Xing, Mengwen; He, Ziting; Sun, Yuanyuan; Deng, Yuqian; Luo, Yongheng; Chen, Xuefang; Cao, Yun; Xiong, Wenbo; Huang, Xinghai; Deng, Pengxin; Luo, Min; et al. (Frontiers in Plant Science, 2024)
Introduction The use of controlled-release nitrogen (N) fertilizers has been shown to improve yield and N-use efficiency (NUE) in mechanical transplanted rice. However, the fertilizer requirements for mechanical direct-seeding rice differ from those for mechanical transplanted rice. The effects of controlled-release fertilizers on yield, NUE, and quality in mechanical direct-seeding rice are still unknown. Methods Hybrid indica rice varieties Yixiangyou 2115 and Fyou 498 were used as test materials, and slow-mixed N fertilizer (120 kg hm-2) as a base (N1), N1+urea-N (30 kg hm-2) once as a base (N2), N1+urea-N (30 kg hm-2) topdressing at the tillering stage (N3), N1+urea-N (30 kg hm-2) topdressing at the booting stage (N4) four N fertilizer management to study their impact on the yield, NUE and quality of mechanical direct-seeding rice. Results and discussion Compared with Yixiangyou 2115, Fyou 498 significantly increased photosynthetic potential, population growth rate, root vigor, and N transport rate by 3.34–23.88%. This increase further resulted in a significant improvement in the yield and NUE of urea-N topdressing by 1.73–5.95 kg kg-1. However, Fyou 498 showed a significant decrease in the head rice rate and taste value by 3.34–7.67%. All varieties were treated with N4 that significantly increase photosynthetic potential and population growth rate by 15.41–62.72%, reduce the decay rate of root vigor by 5.01–21.39%, promote the N transport amount in stem-sheaths (leaves) by 13.54–59.96%, and then significantly increase the yields by 4.45–20.98% and NUE of urea-N topdressing by 5.20–45.56 kg kg-1. Moreover, the rice processing and taste values were optimized using this model. Correlation analysis revealed to achieve synergistic enhancement of high-yield, high-quality, and high-NUE in rice, it is crucial to focus on increasing photosynthetic potential, population growth rate, and promoting leaf N transport. Specifically, increasing the contribution rate of N transport in stem-sheaths is the most important. These findings offer an effective N management strategy for 4R nutrient stewardship (right source, right method, right rate and right timing) of mechanical direct-seeding hybrid indica rice.